Empowering Efficiency: A Web-Based Inventory and Sales Information System for Drinking Water Distributors through Rapid Application Development - Paulus Leonardo; Jansen Wiratama (Journal of Information System and Informatics, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are vital for a country's economy, fostering job creation and economic growth. This research focuses on MSME water distribution agents engaged in selling and distributing various brands and types of bottled drinking water. With a customer base exceeding a thousand and an average of 30 daily transactions, these agents encounter specific challenges in inventory and sales reporting. Presently, MSMEs rely on traditional methods, using books to record stock and sales reports, manually calculating transactions with calculators, and preparing handwritten paper invoices. These practices often result in writing errors, inaccuracies in product information, and pricing inconsistencies. Furthermore, the manual nature of these processes consumes significant time and effort on a daily basis. This study highlights the applicability of the Rapid Application Development (RAD) system design method in creating an efficient and time-sensitive solution. By leveraging RAD, the system design was swiftly accomplished with a limited team. The traceability matrix test validates the successful alignment of the designed information system with the needs of MSME agents in the drinking water distribution sector. The findings of this study provide compelling evidence that the RAD system design approach significantly enhances inventory and sales management practices for MSMEs involved in drinking water distribution. By implementing the developed information system, MSME agents can streamline their operations, eliminate manual errors, and improve overall efficiency, thereby fostering their growth and success in the market.